Reestructuración técnico administrativa del proceso de pre-impresión de la empresa Idéntico S.A.S. (2017)
This document proposes the restructuring of IDéntico S.A.S., whose productive purpose is the manufacture of Pre-printed Cards (TPI). A proposal is implemented to recondition the productive process of the company, which currently presents a deficit in income for different causes. The theoretical support of the proposal and main axis of restructuring is the map of processes, from there the management processes are carried out which allow the directives to inform and approve the proposal; This way the missionary processes of the company are presented, in such a way that new productive purposes are established, which are achieved through a series of restructuring within the company or better known as support processes. The map of processes is applied through the exhaustive analysis of different components of the company, a series of meticulous studies are made in regards to marketing, organization and production (technical), this creates a general diagnosis that allows to observe some of the flaws that are presented in each of the previous studies.